+0  
 
0
97
1
avatar+408 

let π‘“(π‘₯)=π‘₯^2+4 and π‘”(π‘₯)=6π‘₯+7. Evaluate the following:

𝑓(𝑔(0))=

𝑓(𝑔(1))=

𝑔(𝑓(0))=

𝑔(𝑓(1))=

𝑓(𝑔(π‘₯))=

𝑔(𝑓(π‘₯))=

𝑓(𝑓(π‘₯))=

𝑔(𝑔(π‘₯))=

 Apr 18, 2021
 #1
avatar+114082 
+1

I was going to give you a snide comment about asking other people to do all your homework for you.

But instead I will answer one and you can doo all the rest yourself

 

let π‘“(π‘₯)=π‘₯^2+4 and π‘”(π‘₯)=6π‘₯+7. Evaluate the following:

𝑓(𝑔(0))=

 

g(0)=6*0+7=7

f(7)=7^2+4=53

 Apr 18, 2021

4 Online Users